Ant-tended hemiptera in Amazonian myrmecophytes: Patterns of abundance and implications for mutualism function (Hymenoptera: Formicidae) - Lapola, David M. [UNESP]; Bruna, Emilio M.; De Willink, Cristina Granara; Vasconcelos, Heraldo L. (My University, 2005)
We assessed how the abundance of ant-tended Hemiptera associated with two Amazonian myrmecophytes, Tococa bullifera and Maieta guianensis, varied as a function of resident ant species. We collected five species or morpho-species of adult hemiptera in the domatia of M. guianensis, with four of these species also found in Tococa bullifera. Maieta guianensis plants inhabited by Crematogaster laevis had over four-fold more hemiptera in them than plants inhabited by Pheidole minutula. In contrast, the density of hemiptera in Tococa bullifera domatia was independent of the species of ant resident. For each of the two ant species inhabiting Maieta guianensis, there was a positive and significant relationship between the abundance of hemiptera and workers inhabiting a plant. This relationship was also significant and positive for the Tococa bullifera plants inhabited by C. laevis. However, there was no relationship between Azteca worker and hemipteran density, although there was a trend towards a positive relationship. Our results indicate that hemipteran abundance can vary significantly between different myrmecophyte species, but that the nature of this relationship is mediated by the identity of the ant associate. Because hemipterans are herbivores, the costs and benefits of different ant partners to the host plant may vary in ways that are often overlooked.
Keywords: Ant-plants; Azteca; Coccids; Crematogaster laevis; Maieta guianensis; Mealybugs; Melastomataceae; Pseudococcids; Scale insects; Tococa bullifera; Coccoidea; Formicidae; Hemiptera; Hymenoptera; Insecta; Pheidole minutula; Pseudococcidae